ANALISIS KAIDAH-KAIDAH FIQIH MUAMALAH DAN IMPLEMENTASINYA DI INDONESIA - Abdulrahim Habel (AN NUQUD, 2023)
The purpose of this research is to study and analyze the principles of muamalah fiqh that are contained in the book al-Asybah wa an-Nadhair by Imam Jalaluddin al-Suyuthi and its implementation in Indonesia. This type of research is library research, the data used is qualitative data obtained from a book study (book study) for 2 years, especially on the principles of muamalah fiqh. The method used in this thesis is descriptive-analytic-implementative, namely determining, describing, and objectively classifying the data being studied as well as interpreting the data, then the data that has been analyzed are compared to find common ground. Jalaluddin Abdurrahman bin Abi Bakr al-Suyuthi is a high priest, hadith expert, accomplished historian as well as linguist and a prolific writer. Imam al-Suyuthi was awarded by Allah Almighty the breadth of knowledge in seven different fields of religious knowledge, namely the science of interpretation, science of hadith, science of fiqh, science of nahwu, knowledge of ma'ani, science of bayan and science of badi '. In fact, he was so confident in giving himself superiority in front of the general public, he said, "In fact, my mastery of these seven sciences has not matched even among my teachers, except fiqh and history." The result of this research is that the method of istinbath al-Suyuthi in extracting the law of fiqh is not only referring to the Al-Qur'an and as-Sunnah as the main source, but al-Suyuthi also uses the comparative Madzhab approach (Hanafiyyah, Malikiyyah, Syafi ' iyyah and Hanabilah) which of course cannot be doubted the validity of which is comprehensive enough, so that it can give birth to fiqh principles that can be accepted among Muslim communities in general throughout the world, and even in Indonesia it has been made part of his fiqh principles as a valid legal product of fiqh. . Meanwhile, the correlation between fiqh al-Suyuthi and contemporary muamalat practice in Indonesia is still very relevant. Because among the 137 DSN-MUI fatwas (Fatwa 137 / DSN-MUI / IX / 2020) using 30% of the principles of al-Suyuthi fiqh